Analysis of antibiotic-induced drug resistance of Salmonella enteritidis and its biofilm formation mechanism. Issue 2 (20th December 2021) - Dai, Weiping; Zhang, Yuliang; Zhang, Jianfeng; Xue, Chengyu; Yan, Jun; Li, Xin; Zheng, Xiaohua; Dong, Rui; Bai, Jing; Su, Yi; Xie, Pinghui; Zhong, Weiming; et al.
ABSTRACT: This research was to explore antibiotic-induced drug resistance of Salmonella enteritidis and its biofilm formation mechanism. Kirby-Bauer (K-B) disk method recommended by Clinical and Laboratory Standards Institute (CLSI) was used to test drug sensitivity of Salmonella enteritidis to 16 kinds of antibiotics including ß-lactams, aminoglycosides, quinolones, sulfonamides, chloramphenicols, and tetracyclines. Polymerase chain reaction (PCR) was performed to detect carrying of drug resistance genes of 29 kinds of antibiotics including ß-lactams, aminoglycosides, quinolones, sulfonamides, chloramphenicols, and tetracyclines of Salmonella enteritidis . The expressions of esp, ebpA, ge1E, and fsrB genes in biofilm group and plankton group were detected when Salmonella was induced, and difference of gene expression was detected by FQ-PCR. The drug resistance rates of Salmonella enteritidis to nalidixic acid, ampicillin, streptomyces, and cefoperazone were high, which were 94.5%, 75%, 67%, and 52%, respectively. 94 strains of Salmonella enteritidis formed 22 kinds of drug resistance spectrum, the strains were generally resistant to 4-5 antibiotics, and some strains formed fixed drug resistance spectrum as follows: AMP-CFP-STR-NA-TE (22.6, 21.7%), AMP-STR-NA-TE (17, 16%), and AMP-CFP-STR-NA (11.1, 10.6%). During biofilm formation, fsr can increase expression of ge1E and decrease expression of esp and ebpA. Consequently, Salmonella enteritidis was generally resistant to nalidixic acid, ampicillin, and streptomycin, and the multidrug resistance was severe. The drug resistance genes sul2, sul3, blaTEM-1-like, tet(A), and tet(G) were highly carried in Salmonella enteritidis . Esp, ebpA, ge1E, and fsrB genes were closely related to biofilm formation of Salmonella enteritidis . Graphical abstract: uf0001